BRANDING UMKM PEMBUATAN SABUN PENCUCI PIRING DAN PEMBUATAN MEDIA TANAM UNTUK MENANAM KANGKUNG HIDROPONIK DI DUSUN BARNUNG DESA JANJI KABUPATEN LABUHANBATU - Rohani, Safaridah Rambe, Mila Nirmala Sari Hasibuan, Ali Akbar Ritonga, Widya Lestari (PT.JNDI, JURNAL BIMA, 2023)
This service aims to (1) provide solutions to the problems faced by UMKM, Making Dishwashing Soap and, Making Planting Media for Planting HYDROPONIC Water Spinach, (2) helping UMKM owners and Farmer Groups to be able to make planting media using hydroponics. Participants in this activity were from the people of Barnung Hamlet, Janji Village, West Bilah District, Labuhanbatu Regency. The method used in this activity is through counseling and outreach to the community. As a result of this activity, it is hoped that people will be able to make their own dishwashing soap at home so that they can reduce their budget and people can grow crops using hydroponic growing media in their own homes.